Fast clean-up and selective enrichment of florfenicol in milk by restricted access media molecularly imprinted magnetic microspheres based on surface-initiated photoiniferter-mediated polymerization. Issue 19 (5th May 2016) - Lv, Yun-Kai; Zhang, Jing; Li, Meng-Zhe; Zhou, Shao-Dan; Ren, Xing-Hui; Wang, Jing
Abstract : A novel RAM-MIMM with water-compatible, exclusion biomacromolecules and selective enrichment analytes was prepared using a surface-initiated iniferter technique for magnetic dispersion extraction of trace florfenicol from milk samples. Abstract : A novel restricted-access media molecularly imprinted magnetic microsphere (RAM-MIMM) was prepared by an initiator-transfer agent-terminator (iniferter) method. The iniferter was synthesized by coating magnetic nanoparticles with silica-gel, modifying them with an amino-group and reacting with 4-(chloromethyl)benzoyl chloride and sodium diethyldithiocarbamate. The molecularly imprinted magnetic microsphere (MIMM) was prepared using florfenicol (FF) as the template, itaconic acid (ITA) as the functional monomer, ethylene dimethacrylate (EDMA) as the cross-linker, and the iniferter as the surface initiator in anhydrous ethanol solvent. The hydrophilic external layer of the MIMM was formed by iniferter polymerization using glycidyl methacrylate (GMA) as monomer, followed by hydrolysis of the linear poly(GMA). The obtained RAM-MIMMs were characterized by TEM, TGA, FT-IR and adsorption experiments. The Fe3 O4 magnetic microspheres were demonstrated to have average diameters around 230 nm and coating thicknesses in the range 20–30 nm. The RAM-MIMMs exhibited high selectivity (1.68) with respect to the imprinted cavities and a hydrophilic external surface with water compatibility and exclusion biomacromolecules. The RAM-MIMMs were used for magnetic dispersion extraction of FF from milk samples. Average recoveries were in the range 85.4–94.7% with a precision of 2.95–4.97%. The limits of detection and quantitation of the proposed method were in the ranges 4.40–18.31 μg kg −1 and 14.66–61.02 μg kg −1, respectively. The proposed method was successfully applied to fast clean-up and selective enrichment of florfenicol in milk.